Issues on enforcement of Islamic criminal law in Malaysia - Ab Aziz, Shamrahayu (Malik Teraju Ria, 2011)
Enforcement of Islamic criminal law is always at the center stage. Most of the time, magnetizes media publicity. At times, it becomes controversial. Thus, many depressing statements have been hurled against Islamic criminal law and its enforcement. Some question the status of Islamic criminal law in the Malaysian legal framework. Some others contend that the enforcement violates individuals' privacy. Some dispute the legal authority of the Religious Enforcement Officers in conducting their investigating powers. This book attempts to discuss these issues objectively by looking at the relevant legal provisions, including the Federal Constitution.